442 Effects of poor maternal nutrition during gestation on the offspring muscle metabolome. (7th December 2018) - Martin, D; Jones, A; Hoffman, M; Pillai, S; Govoni, K; Zinn, S; Reed, S
Abstract: Poor maternal nutrition during gestation alters offspring muscle composition, fiber number, and postnatal growth. Additionally, poor maternal nutrition impacts offspring whole body and stem cell metabolism. We hypothesized that over- or restricted-feeding ewes during gestation would alter the offspring longissimus muscle metabolome. Pregnant Western White-faced ewes (n = 47) were individually fed 60% (restricted), 100% (control), or 140% (over) of NRC requirements for TDN starting at d 30.2 ± 0.2 of gestation. At days 90 and 135 of gestation, ewes were euthanized for fetal muscle collection. Another group of ewes were allowed to lamb and offspring were necropsied within 24 h of birth. Mass spectrophotometry of longissimus muscle samples (n = 8 fetuses per treatment per time point) identified 612 metabolites. Data were analyzed by ANOVA for main effects of treatment, time point, and their interaction. Compared with controls, maternal over-feeding altered metabolites in 63 pathways and maternal restricted-feeding altered metabolites in 56 pathways (P < 0.05). Maternal over-feeding decreased concentrations of 1 phosphatidylcholine (PC) metabolite at d 90, 2 PC metabolites at d 135, and 4 PC metabolites at birth compared with controls (P < 0.05). Additionally, at d 135, maternal overfeeding increased 1 phosphatidylethanolamine (PE) metabolite while reducing 10 PE metabolites at birth compared with controls (P < 0.05). Offspring from overfed ewes had decreased concentrations of 12 lysolipids at birth compared with controls (P < 0.05). Maternal restricted-feeding increased expression of reduced glutathione 3.07-fold at d 90 (P = 0.008), whereas at d 135, oxidized glutathione was decreased 0.21-fold compared with control (P = 0.03). Thus, maternal over-feeding may promote increased lipid oxidation in offspring muscle, which may predispose offspring to altered lipid utilization and storage postnatally. Maternal restricted-feeding resulted in alterations in glutathione metabolism, potentially indicative of changes to redox status in these offspring.